Analisis Frasa dalam Teks Esai pada Buku Bahasa Indonesia Kelas XII Kurikulum Merdeka (International Forum of Researchers and Lecturers, 2023)
The main discussion in this research article is the analysis of phrases that have a function in observing the use of the types of phrases contained in the essay text entitled